Pengaruh model pembelajaran make a match berbantuan wordwall terhadap hasil belajar IPAS peserta didik kelas IV SDN 2 beriBeringin Raya - Dika Ramadhona, Zahra; Fernando Rizqi, Yoga; Khairani, Fadhilah; Herpratiwi (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
Abstrac The learning models and media used by educators have an impact on student learning outcomes. The purpose of this study was to analyze the influence and differences between the make a match learning model assisted by wordwall and powerpoint on students' learning outcomes. The research method used was a quasi-experimental design. The population of the study was students in grade IV of SDN 2 Beringin Raya with a total of 60 students. The sample used was 60 students with sampling using simple random sampling techniques and data collection using tests and observations. Data analysis used the t-test. Based on the results of the study, it can be concluded that: (1) there is a significant influence of the application of the make a match learning model assisted by wordwall on students' learning outcomes. (2) There was a significant influence of the application of the make a match learning model assisted by PowerPoint on the results of students' science learning. 3) There was a difference in the influence of the application of the make a match learning model assisted by word walls and assisted by PowerPoint on the results of students' science learning.